2022
DOI: 10.1186/s42269-022-00711-5
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil from Cymbopogon citratus exhibits “anti-aspergillosis” potential: in-silico molecular docking and in vitro studies

Abstract: Background Aspergillosis, has recently confounded some states of India. Due to major role in fungal cell wall synthesis, in the present study UDP-glycosyltransferase, Glucosamine-6-phosphate synthase and chitin synthase were chosen as an appropriate sites to design drug. The objective of present study was molecular docking of lemon grass essential oil component citral and in vitro validation. GC-FID analysis was used to find out aromatic profile. For docking, Patch-dock analysis was used. Ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The major chemical compositions of EOs are terpenes, aldehydes, and phenols ( Boubaker et al, 2016 ; Sharma and Kaur, 2022 ). Research have reported that EO’s with monoterpenes and sesquiterpenes exhibit antifungal activities against several fungi ( Tian et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…The major chemical compositions of EOs are terpenes, aldehydes, and phenols ( Boubaker et al, 2016 ; Sharma and Kaur, 2022 ). Research have reported that EO’s with monoterpenes and sesquiterpenes exhibit antifungal activities against several fungi ( Tian et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…C. citratus , or lemongrass, exhibits a wide range of biologic activities due to its diverse bioactive compounds. The plant’s antimicrobial properties encompass both antibacterial and antifungal actions, with efficacy against Gram-negative and Gram-positive bacterial strains [ 4 ] and fungi such as Aspergillus spp., Mucor indicus [ 5 ], Botrytis cinerea [ 6 ], and Aspergillus flavus and Aspergillus parasiticus [ 7 ]. Lemongrass demonstrates anti-aspergillosis potential by inhibiting enzymes essential for fungal cell wall synthesis [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The plant’s antimicrobial properties encompass both antibacterial and antifungal actions, with efficacy against Gram-negative and Gram-positive bacterial strains [ 4 ] and fungi such as Aspergillus spp., Mucor indicus [ 5 ], Botrytis cinerea [ 6 ], and Aspergillus flavus and Aspergillus parasiticus [ 7 ]. Lemongrass demonstrates anti-aspergillosis potential by inhibiting enzymes essential for fungal cell wall synthesis [ 4 , 5 , 6 , 7 , 8 ]. Lemongrass also shows promise in the realm of human health, with hepatoprotective effects against hepatocellular injury in diabetic rats [ 9 ], cholesterol-lowering potential by preventing gut absorption [ 10 ], and the ability to overcome doxorubicin resistance in cancer cells [ 11 ].…”
Section: Introductionmentioning
confidence: 99%